1992
DOI: 10.1002/j.1537-2197.1992.tb13752.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Genotype and Ploidy Level on Pollen Surface Sculpturing in Maize (Zea Mays L.)

Abstract: Pollen exine sculpturing is a consistent feature of seed plant taxa, yet no mechanism for control of sculpturing pattern has been found. On grass pollen, exine sculpturing takes the form of closely packed spinules. Exine spinules on pollen grains from six maize populations representing all combinations of three genetic backgrounds (single cross hybrids W22 W23, N6 W23, R75 W23) and two ploidy levels (2x, 4x) were examined by scanning electron microscopy. Doubling ploidy levels from 2x to 4x increased pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The ploidy level and genotypes of both the gametophyte and the sporophyte in which the pollen grains are formed determine the size of the pollens (Ottaviano and Mulcahy 1989;Southworth and Pfahler 1992;Katsiotis and Forsberg 1995b). Our research on 15 oat accessions showed a statistically significant correlation between ploidy and the length of pollen grains.…”
Section: Discussionmentioning
confidence: 51%
“…The ploidy level and genotypes of both the gametophyte and the sporophyte in which the pollen grains are formed determine the size of the pollens (Ottaviano and Mulcahy 1989;Southworth and Pfahler 1992;Katsiotis and Forsberg 1995b). Our research on 15 oat accessions showed a statistically significant correlation between ploidy and the length of pollen grains.…”
Section: Discussionmentioning
confidence: 51%
“…It is well known that cell volume increases with increasing DNA content, which may, in turn, influence pollen diameter (Tan & Dunn, 1973;Lewis, 1980;Tal, 1980;Pundir, Rao & Van Der Maesen, 1983;Fagerberg, Davis & Matthews, 1990;Van Dijk & Van Delden, 1990;Bamberg & Hanneman, 1991;Berdahl & Barker, 1991;Humbert-Droz & Felber, 1992;Southworth & Pfahler, 1992;Jansen & Den Nijs, 1993). Becauseof the relatively close correlation between 'giant, big' pollen and 2n status (Orjeda, Freyre & Iwanaga, 1990;Veronesi, Tavoletti & Mariani, 1990;Maceira et al, 1992), the presence of giant grains has frequently been used as an indication of the production of 2n pollen (Den Nijs & Peloquin, 1977a, b;Vorsa & Bingham, 1979;Camadro & Peloquin, 1980;McCoy, 1982;Ramanna, 1983;Den Nijs & Stephenson, 1988;Van Santen, 1988;Veronesi, Mariani & Tavoletti, 1988;Den Nijs & Winkelhorst, 1989;Sala et al, 1989;Van Tuyl et al.…”
Section: Morphological Screening To Detect 2n Pollenmentioning
confidence: 99%
“…In relation to size differences of pollen grains, chromosome data should also be analysed, since larger pollen grains are often a result of polyploidy, following the tenet that polyploidy generates larger cells and therefore larger pollen grains (Bronckers, 1963;Stebbins, 1971;Muller, 1979;Southworth & Pfahler, 1992). A detailed chromosome survey of Palaua is still wanting; however, preliminary data (Schneider & Huertas, unpubl.…”
Section: Infrageneric Variability and Taxonomic Utilitymentioning
confidence: 99%